Figures do matter: A literature review of 4587 robotic pancreatic resections and their implications on training. (1st September 2022) - Levi Sandri, Giovanni B.; Abu Hilal, Mohammed; Dokmak, Safi; Edwin, Bjørn; Hackert, Thilo; Keck, Tobias; Khatkov, Igor; Besselink, Marc G.; Boggi, Ugo; ,
Abstract: Background: The use of robotic assistance in minimally invasive pancreatic resection is quickly growing. Methods: We present a systematic review of the literature regarding all types of robotic pancreatic resection (RPR). Our aim is to show for which procedures there is enough experience to permit safe training and provide an estimation of how many centers could serve as teaching institutions. Results: Sixty‐four studies reporting on 4587 RPRs were analyzed. A total of 2598 pancreatoduodenectomies (PD) were reported by 28 centers from Europe (6/28; 21.4%), the Americas (11/28; 39.3%), and Asia (11/28; 39.3%). Six studies reported >100 robot PD (1694/2598; 65.2%). A total of 1618 distal pancreatectomies (DP) were reported by 29 centers from Europe (10/29; 34.5%), the Americas (10/29; 34.5%), and Asia (9/29; 31%). Five studies reported >100 robotic DP (748/1618; 46.2%). A total of 154 central pancreatectomies were reported by six centers from Europe (1/6; 16.7%), the Americas (2/6; 33.3%), and Asia (3/6; 50%). Only 49 total pancreatectomies were reported. Finally, 168 enucleations were reported in seven studies (with a mean of 15.4 cases per study). A single center reported on 60 enucleations (35.7%). Results of each type of robotic procedure are also presented. Conclusions: Experience with RPR is still quite limited. Despite high case volume not being sufficient to warrant optimal training opportunities, it is certainly a key component of every successful training program and is a major criterion for fellowship accreditation. From this review, it appears that only PD and DP can currently be taught at few institutions worldwide.